1979
DOI: 10.1080/15298667991430721
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lifting capacity

Abstract: As science and technology become more sophisticated and with the rapid computation capabilities of the modern computer available, it becomes both possible and economically feasible to scientifically study man and his interaction with his working environment. It is now possible for a person seeking employment to expect and obtain a position which will not be unnecessarily hazardous to his immediate health or have detrimental effects over the long run. Manual materials handling is the contributor of over 400,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…at CARLETON UNIV on July 26, 2015 hfs.sagepub.com Downloaded from 488-August, 1980 mine maximum allowable weights and workloads based on the psychophysical criteria (Snook, 1978;Garg and Saxena, 1979;Ayoub, Dryden, McDaniel, Knipfer, and Dixon, 1979). Arguments in favor of psychophysical methodology state that it is simple to use and understand and that it is only the individual worker who can integrate the various sensory inputs into one meaningful response.…”
Section: Introductionmentioning
confidence: 98%
“…at CARLETON UNIV on July 26, 2015 hfs.sagepub.com Downloaded from 488-August, 1980 mine maximum allowable weights and workloads based on the psychophysical criteria (Snook, 1978;Garg and Saxena, 1979;Ayoub, Dryden, McDaniel, Knipfer, and Dixon, 1979). Arguments in favor of psychophysical methodology state that it is simple to use and understand and that it is only the individual worker who can integrate the various sensory inputs into one meaningful response.…”
Section: Introductionmentioning
confidence: 98%
“…Firefighters reported that such above-shoulder activities were among the most difficult tasks, 1 and this view is consistent with our understanding of mechanical loading, with lower maximal strength observed for lifts above the shoulder. 31,32 Furthermore, because lower-and upper-limb strength are relatively poor predictors of functional, overhead lifting and holding performance, 33 the use of content-valid tests becomes an important consideration in the design of aptitude tests.…”
Section: Movement Class Three: Overhead Pushing and Holdingmentioning
confidence: 99%
“…Psychophysical tests of acceptability have not generally been applied for individual assessment. Garg et al (1980) did not find that acceptable levels could be predicted from isometric strength: though Ayoub et al (1979) were able to make predictions from a variety of anthropometric and strength tests. Griffin et al (1984) therefore studied the repeatability of quickly applied, individual assessments of acceptable lifting weights.…”
Section: Introductionmentioning
confidence: 77%